Hubungan Human, Organisasi, dan Teknologi Terhadap Kepuasan Penggunaan Aplikasi Primary Care Di Klikik Pratama Kota Pekanbaru - Tri Purnama Sari; Wen Via Trisna; Haryani Octaria; Doni Jepisah (Jurnal Manajemen Informasi Kesehatan Indonesia (JMIKI), 2019)
Satisfaction of Primary Care application users becomes the need to guarantee the accountability of services to BPJS. To measure the level of satisfaction of the Primary Care application, the End User Computation Satisfaction (EUCS) method is used. The aim of the study was to study the relationship between humans, organizations, and technology with EUCS (End User Satisfaction Computing at Pekanbaru pratama city clinic. This type of research is a quantitative cross sectional study with primary information system networks. Variables used were factor-independent variables HOT ( human) EUCS (End User Computing Satisfaction) The research subjects were primay care information system operators with a sample of 90 pratama clinics in the city of Pekanbaru that were taken as total samples, which stated that humans were quite good about being satisfied with the use of p care as much as 2 ( 100%), respondents who stated that the organization was good enough about satisfaction with the use of p care, namely as much as 5 (100%), and respondents who stated that the technology was good enough needed to be satisfied with the use of p care, which was 6 (60%).